Short Research Report: Cultivating Communication Skills in Times of Crisis: The perceived impact of SEL techniques in formative assessment on the communication competence of pre-service teachers in Ukraine - Natalia Dmitrenko; Violetta Panchenko; Olena Hladka; Iryna Shkola; Antonina Devitska (International Journal of Emotional Education)
This study examined the integration of social-emotional learning (SEL) in formative assessment of pre-service English as foreign language (EFL) teachers during times of crisis and its perceived impact on their communicative competence. The study encompasses a six-month trial period of SEL-enriched formative assessments across five Ukrainian universities. Findings from interviews with 12 participants indicate that incorporating SEL in EFL teacher education programs enhanced learning outcomes, when compared to traditional assessment methods. Furthermore, data suggest that promoting SEL in formative assessment provides invaluable feedback for tutors, prompting them to modify their teaching strategies appropriately while applying and expanding pre-service EFL teachers’ professional-focused skills.